PENGARUH PROMOSI TERHADAP PENINGKATAN PENJUALAN PADA PT. JUMBO SWALAYAN DI MANADO - TUMIWAN, APRILIA; SUMAMPOUW, HARRY; REVO TAMPI, JOHNY (JURNAL ADMINISTRASI BISNIS (JAB), 2016)
Abstract. In order to maintain the viability of the company, companies are often faced with various problems, such as the difficulty in increasing the volume of sales, the existance of competition from similar companies, the increasing complexity of consumer behaviour towards a product, changing consumer tastes, as well as the uncertain economic conditions. Promotion is an activity that can be performed by the company with the aim to inform, persuade, and influence consumers to choose or buy a product offered by the company.The purpose of this study was to determine the extent of influence of promotion as well as analyze the relationships and the influence of promotions to increase sales in PT. Jumbo Supermarkets in Manado.The method used is the method of associative approach to samples from this study population the visitors jumbo supermarkets purchase transaction product in certain period of time.The results of data analysis showed that; (1) the functional relationship between the promotion of increased sales in supermarket jumbo manado, detected in equation:Ŷ =25,51 +0,28 X1. (2) the regression coefficient (b) as big as 0,28 as big as 0,28 this means that if the sale increased by 1 unit, then the increase in sales at PT. Jumbo Supermarkets Manado will increase by 0,28 unit. (3)southwestern promotion determination to increased sales in supermarket jumbo manado detected 46,5 % whereas 54,5% is determined by other factors that are not observed in this study. It’s recommended that jumbo supermarket manado, (1) need to carry out promotional activities accordingly so that its sales volume continues to increase as planned (2) companies pay attention to the policy of marketing mix, especially the issue price is affordable for consumers, so as to increase its sales volume (3) in the framework of the current era businesses should jumbo supermarkets must maintain and enhance the promotion again so that sales volume increased to more optimal.Keywords: Promotion, Increased Sales